Spatial adjustment of bioenergetics, a possible determinant of contractile adaptation and development of contractile failure - Szibor, Marten; Mühlon, Marie; Doenst, Torsten; Pohjoismäki, Jaakko L. O. (Frontiers in Molecular Medicine, 2023)
Cardiomyocytes depend on mitochondrial oxidative phosphorylation (OXPHOS) for energy metabolism, which is facilitated by the mitochondrial electron transfer system (ETS). In a series of thermogenic redox reactions, electrons are shuttled through the ETS to oxygen as the final electron acceptor. This electron transfer is coupled to proton translocation across the inner mitochondrial membrane, which itself is the main driving force for ATP production. Oxygen availability is thus a prerequisite for ATP production and consequently contractility. Notably, cardiomyocytes are exceptionally large cells and densely packed with contractile structures, which constrains intracellular oxygen distribution. Moreover, oxygen must pass through layers of actively respiring mitochondria to reach the ones located in the innermost contractile compartment. Indeed, uneven oxygen distribution was observed in cardiomyocytes, suggesting that local ATP supply may also vary according to oxygen availability. Here, we discuss how spatial adjustment of bioenergetics to intracellular oxygen fluctuations may underlie cardiac contractile adaptation and how this adaptation may pose a risk for the development of contractile failure.